Spatiotemporally controllable honeycomb superlattice plasma photonic crystals in dielectric barrier discharge. (1st April 2023) - Fan, Weili; Hou, Xiaohan; Jia, Mengmeng; Tian, Miao; He, Yafeng; Liu, Fucheng
Abstract: We present the experimental realization of tunable honeycomb superlattice plasma photonic crystals (PPCs) in dielectric barrier discharge by utilizing mesh-liquid electrodes. Fast reconfiguration among the simple honeycomb lattice, honeycomb superlattice, and honeycomb-snowflake superlattice is achieved. A dynamic control on the sizes of center scattering elements in the honeycomb superlattice has been realized. A phenomenological activator-inhibitor reaction diffusion model is established to demonstrate the formation and reconstruction of the honeycomb superlattice. The simulations reproduce well the experimental observations. The photonic band diagrams of different honeycomb PPCs are studied by using the finite element method. The addition of large center elements in honeycomb superlattice yields remarkable omnidirectional band gaps that are about 2.5 times larger than in the simple honeycomb lattice. We propose an effective scheme to fabricate spatiotemporally controllable honeycomb lattices that enable great improvement in band gap size and dynamic control of microwave radiations for wide applications.